Qaeda al-Yaqinu Laa Yuzaalu Bisyak and its Implementation in Fiqh Law - Faridz Anwar, Ahmad Faridz Anwar1; Djumhur Salikin, Adang (Jurnal Legisci, 2023)
The fundamentals of Islamic law, or usul fiqh, must be learned as part of the fiqh study process. Al-Yaqinu Laa Yuzaalu Bisyak, which translates to "certainty is not removed by doubt," is one of the tenets of usul fiqh. The descriptive qualitative approach of research is thought to be appropriate for this piece of literature. The law of something remaining is known as yaqn li yazl bi al-syak and is based on the conviction that it cannot be eliminated unless there is a convincing reason and that it is not necessarily doomed to disappear simply because a doubt surfaces. The Word of Allah SWT, found in Quranic letter Ynus verse 36, serves as the legal foundation for the reign of al-Yaqn li Yazl bi al-Syak. Additionally, there is the Hadith regarding the person who feels something in his prayer as well as the Word of Allah (swt) in Surah Al-Najm Verse 28 of the Quran. The application of the fiqh's al-Yaqn l'Yazl bi al-Syak norm can be seen in the following areas: ablutions, payables, marriage contracts, and flowers. Qaidah Al-Yaqinu Laa Yuzaalu Bisyak and Its Implementation in Fiqh Law is the title of this study.